2011
DOI: 10.1242/jcs.087114
|View full text |Cite
|
Sign up to set email alerts
|

Mutations associated with Charcot–Marie–Tooth disease cause SIMPLE protein mislocalization and degradation by the proteasome and aggresome–autophagy pathways

Abstract: SummaryMutations in SIMPLE cause an autosomal dominant, demyelinating form of peripheral neuropathy termed Charcot-Marie-Tooth disease type 1C (CMT1C), but the pathogenic mechanisms of these mutations remain unknown. Here, we report that SIMPLE is an early endosomal membrane protein that is highly expressed in the peripheral nerves and Schwann cells. Our analysis has identified a transmembrane domain (TMD) embedded within the cysteine-rich (C-rich) region that anchors SIMPLE to the membrane, and suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
115
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(126 citation statements)
references
References 80 publications
(115 reference statements)
9
115
2
Order By: Relevance
“…misfolded SIMPLE is not cleared by ERAD 3 indicates that CMT pathogenesis can be mediated by dysfunction in ERADindependent pathways. Proteasome impairment induced by misfolded and aggregated proteins was observed in several mouse models of demyelinating CMT1A.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…misfolded SIMPLE is not cleared by ERAD 3 indicates that CMT pathogenesis can be mediated by dysfunction in ERADindependent pathways. Proteasome impairment induced by misfolded and aggregated proteins was observed in several mouse models of demyelinating CMT1A.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 How misfolding of these membrane proteins with different topologies contributes to demyelinating neuropathy remain unknown. We found that misfolded SIMPLE forms abnormal cytosolic aggregates and mediates erroneous interactions with cellular proteins, 3 which are pathogenic mechanisms characteristic of many protein-misfolding diseases. 11,12 These findings suggest that demyelinating CMT may be a proteinmisfolding disease of Schwann cells.…”
Section: P Eripheral Neuropathies Such As Charcot-mentioning
confidence: 98%
See 3 more Smart Citations